Mapping between headache specific and generic preference-based health-related quality of life measures - Khan, K; Mistry, H; Matharu, M; Norman, C; Petrou, S; Stewart, K; Underwood, M; Achana, F (BioMed Central, 2022)
Background The Headache Impact Test (HIT-6) and the Chronic Headache Questionnaire (CH-QLQ) measure headache-related quality of life but are not preference-based and therefore cannot be used to generate health utilities for cost-effectiveness analyses. There are currently no established algorithms for mapping between the HIT-6 or CH-QLQ and preference-based health-related quality-of-life measures for chronic headache population.